Reaction of ethylene over a typical Fischer‐Tropsch synthesis Co/TiO2 catalyst - Yusheng Zhang; Mgcini Tshwaku; Yali Yao; Jianli Chang; Xiaojun Lu; Xinying Liu; Diane Hildebrandt (Engineering Reports, 2020)
Abstract In order to identify the potential reaction paths of C2H4 and their product distribution in Fischer‐Tropsch synthesis (FTS), a series of experiments were designed over a Co/TiO2 catalyst in the absence of CO. C2H4 did quickly react with H2 to produce C1‐6 products under Fischer‐Tropsch (FT) reaction conditions. Although the dominant reaction is C2H4 hydrogenation to ethane, changing the reaction conditions (temperature and partial pressure of reactants) can lead to the other reaction pathways being enhanced, resulting in varying product selectivity to both linear and branch olefins and paraffins. Possible reaction pathways had been summarized and discussed, which including C2H4 reaction to ethylidene followed by dimerization; C2H4 insertion into C2 surface species and dimerization and C4 decomposition and/or direct C2 hydrogenolysis. Furthermore, the products obtained from C2H4 reactions were fit to a typical FTS product distribution, which indicate that both the chain growth initiators and monomers are not necessarily only derived from hydrogenation of CO but also from the secondary reactions of olefins.